Penerapan model problem-based learning untuk meningkatkan hasil belajar matematika siswa - Widyastuti, Putri; Solfitri, Titi; Armis (Jurnal Pendidik Indonesia, 2025)
This study aims to improve mathematics learning outcomes through the implementation of the Problem-Based Learning (PBL) model. The subjects of this study were students of class VIII-C at SMP Negeri 1 Kerumutan in the even semester of the 2024/2025 academic year, consisting of 17 male and 14 female students. The research instruments included learning tools and data collection instruments. The learning tools comprised the Learning Objectives Flow and Teaching Modules, while the data collection instruments consisted of observation sheets and mathematics learning outcome tests. Based on the analysis of students' learning outcomes, there was a significant improvement from the baseline score (before the action) to cycle I and cycle II. At the baseline, only 8 students (25.80%) achieved the minimum mastery criteria, which increased to 17 students (54.83%) in cycle I, and 19 students (61.29%) in cycle II. These findings indicate that the implementation of the Problem-Based Learning model effectively improves the learning process and enhances mathematics learning outcomes on statistics material in class VIII-C of SMP Negeri 1 Kerumutan during the 2024/2025 even semester.